Tourism research in Malaysia what,which way and so what? - Din, Kadir; Mapjabi, Jabil (Universiti Utara Malaysia Press, 2010)
This collection offers a sample of contemporary works on tourism and its impact on the Malaysian environment, written by academics from a variety of perspectives.Given the growing body of literature on different aspects of the industry the coverage is by no means representative, let alone exhaustive, of the current discourse.Nonetheless the nineteen chapters cover a range of interests and concerns which have emerged as a consequence of spectacular growth in tourist arrival which currently places Malaysia as one of the most popular destinations in Asia.Recent forecast indicates that the growth trends will continue for at least another decade before the country as a destination approaches maturity.This volume would be a useful reference for students, academic and other researchers who are looking for detailed information to enable them to analyse the impacts and implications of tourism development on the host society.